The Effect of Group Competitive Learning Style on Learning Some Fundamental Skill In First Grade Se3condry School Students - Hassan, Mohammed; Mohammed Ali, Yousif (Journal of Physical Education, 2018)
The Effect of Group Competitive Learning Style on Learning Some Fundamental Skill In First Grade Se3condry School StudentsThe importance of the reseache4 lies in teaching some fundamental skills in soccer using a new style of learning. The problem of the research lies in the students taking a long time learning the basic skills following the traditional method resulting in weakness in skill performance. The researcher aimed at identifying the effect of group competitive style in learning some fundamental skills in soccer. The researchers hypothesized significant statistical operations between pre and posttests for both groups in favor of the experimental group in posttests. The researchers used the experimental method and applied on a group of first grade secondary school students 2017 – 2018. The researchers concluded that posttests surpassed posttests showing significant differences in experimental group and that the group competitive learning style has a positive effect on the students. Finally they recommended using this style in developing the students' fundamental skills.